IFRS ACCOUNTING POLICY AS AN AUDITOR’S INFORMATION - Karpachova, Olga (Socio-economic relations in the digital society, 2020)
An important issue at the beginning of the audit task is the information support of the auditor, which will be the basis for work. Such a basis for the audit of enterprises that prepare their reports according to both national standards and international standards is the company’s accounting policy. An audit of accounting policies helps to establish compliance with international standards and applicable laws, as well as the nature of the enterprise. That is, the main purpose of the audit of accounting policy is to study the internal documents of the enterprise governing the organization and conduct of accounting. As auditing practice shows, companies that have moved to international standards in most cases do not have an accounting policy that would fully meet the requirements of international financial reporting standards. The auditor in performing the task of auditing the following accounting policy must establish the presence of a management order to adopt the accounting policy of the enterprise; determine the compliance of the adopted accounting policy with the requirements of international standards and current legislation; to study compliance with the assumptions and requirements established by regulatory documents when developing an order on accounting policy; to investigate the completeness of the disclosure of selected in the formation of accounting policies of accounting methods that significantly affect the assessment and decision-making of users of accounting, analyze and evaluate the general and specific elements of accounting policy. This article explores the accounting policies developed in accordance with the requirements of international standards as an information support of the auditor. The purpose and objectives of the audit of accounting policies are studied. The requirements of international standards for accounting policy and disclosure are considered. The conclusion on the importance of accounting policy as information support of the auditor is formed.